Morphological variations during the development of somatic embryos of tea (Camellia sinensis L.) in vitro Keragaman morfologi selama perkembangan embrio somatik teh (Camellia sinensis L.) in vitro - . SUMARYONO; Imron RIYADI; J.S. TAHARDI (Menara Perkebunan, 2001)
SummarySomatic embryo culture of tea (Camelliasinensis L.) on an agar-solidified medium consistsof embryos of different sizes, colors anddevelopmental stages. One gram of mostly globularsomatic embryos were cultured on a solidproliferation medium of WP containing 57.1 µMIAA and 4.4 µM BAP to observe theirmorphological variations with respect to embryosize, color, and developmental stage over oneculture passage of 6 weeks. Fresh weight ofsomatic embryos increased slowly during the first4 weeks and then sharply thereafter. At the fourthweek, the number of embryos increasedconsiderably although their weight did not increase,indicating the formation of secondary embryos.The average size of tea somatic embryos did notchange significantly over the culture period,however, the embryo size was already highly variedat the start and increased as the embryo developed.About one half of the embryos were yellowish and the rest were divided equally between the greenishand reddish embryos. At the initial culture, 60% ofthe embryos were at the globular, 30% at heart and10% at torpedo stage. Generally, globular embryosdeveloped into later-stage embryos as the cultureprogressed, however, on this proliferation mediumalmost 80% of the embryos remained at the globularand heart-shaped stages even after the sixth week.If single globular somatic embryos with a particularcolor were cultured on a solid regeneration mediumof WP with 0.47 µM kinetin, 0.69 µM ABA and0.29 µM GA 3 , some of them especially theyellowish embryos underwent color change. Mostof these single globular embryos developedgradually into the later stages. While the initialcolors of embryos affected the rate ofdevelopmental stage changes, yellowish globularembryos tended to develop more rapidly intocotyledonary or germinant stages than the greenishand reddish embryos.RingkasanBiak embrio somatik tanaman teh (Camelliasinensis L.) pada medium padat terdiri dari embriodalam berbagai ukuran, warna dan stadiaperkembangan. Satu gram embrio somatik yangsebagian besar dalam stadia globuler telahdibiakkan pada medium padat proliferasi (mediumWP dengan IAA 57,1 µM dan BAP 4,4 µM) untukmengamati keragaman morfologi embrio dalam halukuran, warna dan stadia perkembangan dalamsatu periode kultur 6 minggu. Berat basah embriosomatik meningkat perlahan pada 4 minggupertama kemudian meningkat dengan tajam. Padaminggu keempat, jumlah embrio melonjakwalaupun beratnya tidak meningkat, hal inimenunjukkan adanya pembentukan embriosekunder. Ukuran rata-rata embrio somatik tidakberubah secara nyata selama periode kultur, tetapiukuran embrio sudah sangat beragam sejak awalkultur dan terus meningkat sejalan denganberkembangnya embrio. Sekitar setengah dariembrio berwarna kuning dan sisanya terdiri dariembrio berwarna hijau dan merah. Pada awalkultur, 60% embrio berada pada stadia globuler,30% stadia bentuk-hati dan 10% stadia bentuk-torpedo. Pada umumnya embrio globulerberkembang ke stadia lebih lanjut sejalan denganwaktu, tetapi pada medium proliferasi ini hampir80% embrio masih dalam stadia globuler danbentuk-hati pada minggu keenam. Apabila embriosomatik globuler tunggal dengan warna tertentudibiakkan pada medium padat regenerasi(WP dengan kinetin 0,47 µM, ABA 0,69 µM danGA 3 0,29 µM, sebagian embrio terutama embriokuning akan mengalami perubahan warna.Sebagian besar embrio globuler tunggal iniberkembang secara bertahap kestadia per-kembangan lebih lanjut. Warna awal embrioberpengaruh terhadap kecepatan perubahan stadiaperkembangan embrio, dengan embrio globulerawal warna kuning cenderung lebih cepatberkembang kestadia kotiledon dan kecambahdibandingkan dengan embrio hijau dan merah.